INTRAVITREAL ANTI–VASCULAR ENDOTHELIAL GROWTH FACTOR TREATMENT AT 2-MONTH INTERVALS REDUCES FOVEAL AVASCULAR ZONE ENLARGEMENT AND VISION LOSS IN RADIATION MACULOPATHY: A Pilot Study. Issue 8 (August 2019) - Daruich, Alejandra; Matet, Alexandre; Schalenbourg, Ann; Zografos, Leonidas
Abstract : Purpose: To evaluate, in eyes with radiation maculopathy, the effect of 2-month-interval anti–vascular endothelial growth factor therapy on best-corrected visual acuity and foveal avascular zone (FAZ) enlargement using optical coherence tomography angiography. Methods: Consecutive treatment-naive patients with radiation maculopathy after proton beam irradiation for choroidal melanoma were retrospectively included. Clinical and optical coherence tomography angiography data at baseline and the 6-month visit were recorded. Two independent observers measured FAZ area manually on 3 × 3-mm optical coherence tomography angiography images of the superficial capillary plexus and deep capillary plexus. Patients were encouraged to follow strictly a 2-month-interval intravitreal anti–vascular endothelial growth factor treatment by either bevacizumab or ranibizumab. Findings were analyzed based on the adherence to the treatment scheme. Results: According to the adherence to the bimonthly anti–vascular endothelial growth factor treatment protocol, patients were categorized into 3 groups: treatment protocol (n = 19, strict adherence), variable intervals (n = 11, intervals other than 2 months), and no treatment (n = 11). The estimated radiation dose to the foveola in each group was 49 ± 16, 46 ± 17, and 46 ± 18 cobalt gray equivalent, respectively ( P = 0.85). For the entire cohort, best-corrected visual acuity loss ( P < 0.02) and FAZ enlargement ( P < 0.0001) were observed over 6 months. Best-corrected visual acuity loss was significantly less pronounced in the treatment-protocol group than in the variable-interval and no-treatment groups ( P = 0.007 and P = 0.004). The FAZ enlargement was lower in the treatment-protocol group compared with the variable-interval group for both superficial capillary plexus ( P = 0.029) and deep capillary plexus ( P = 0.03), and to the no-treatment group for the deep capillary plexus only ( P = 0.016). Conclusion: Decrease in best-corrected visual acuity and FAZ enlargement on optical coherence tomography angiography occurred over 6 months in eyes with radiation maculopathy and were significantly reduced under 2-month-interval anti-vascular endothelial growth factor therapy. Abstract : Intravitreal anti–vascular endothelial growth factor therapy at 2-month intervals reduce visual acuity loss and foveal avascular zone enlargement in patients with radiation maculopathy during a 6-month follow-up.